Comparison of citrated and fresh whole blood for viscoelastic coagulation testing during elective neurosurgery. Issue 156 (August 2017) - Silverberg, E.; Tornqvist, F.; Kander, T.; Bengzon, J.; Solomon, C.; Bonnevier, J.; Schött, U.
Abstract: Background: Previous viscoelastic haemostatic tests studies have often indicated a hypercoagulative test signal with citrated blood, which could influence clinical decision makings. Purpose: The aim of this study was to compare fresh and citrated whole blood using two non-automated viscoelastic ROTEM and Sonoclot tests. Our hypothesis was that citrated blood would demonstrate a hypercoagulative response in this setting, not tested before. Methods: Perioperative viscoelastic coagulation changes were evaluated with a ROTEM and Sonoclot in 38 patients undergoing elective brain tumor surgery. The citrated samples were recalcified with CaCl2 . Wilcoxon nonparametric-paired tests and Bland-Altman plots were performed to compare the fresh and citrated blood analyses. Results: The citrated blood showed a hypercoagulative response in ROTEM NATEM-clot formation time and α-angle, Sonoclot-clot rate and platelet function, as compared to fresh blood (p < 0.0001). Conclusions: Fresh whole blood may theoretically reflect in vivo haemostasis more closely than citrated analyses, which indicated a hypercoagulative response as compared to the fresh whole blood analyses Bland-Altman plots also indicated that ROTEM reference ranges in patients undergoing brain surgery should be redefined. Future studies must establish the correlation between viscoelastic test results using fresh or citrate anticoagulated blood and clinical outcomes, such as bleeding, transfusion or reoperation for postoperative haematoma. Graphical abstract: Highlights: Citrated blood gives a hypercoagulative viscoelastic test response as compared to fresh blood in neurosurgery patients. This difference probably relates to different test parameter normal ranges that need to be better defined. The differences between viscoelastic test results using fresh or citrated blood and clinical outcomes should be defined.